МЕТОД СИНТЕЗА ЗАМКНУТЫХ СИСТЕМ АКТИВНОГО ЭКРАНИРОВАНИЯ МАГНИТНОГО ПОЛЯ ВОЗДУШНЫХ ЛИНИЙ ЭЛЕКТРОПЕРЕДАЧИ - Кузнецов, Б.И.; Туренко, А.Н.; Никитина, Т..Б.; Волошко, А.В.; Коломиец, В.В. (Інститут електродинаміки НАН України, Київ, 2016)
The method of synthesis of closed-loop systems of active screening of power frequency magnetic field generated by overhead lines inside located near residential buildings. The synthesis based on the problem of multiobjective optimization of system parameters at which the calculation of the objective function vector is performed on the basis of the Biot - Savart law. This problem is solved by multiswarm stochastic multi-agent optimization. The results of the synthesis of the active screening system of the rotating magnetic field with an efficiency of at least 4. References 6, figures 2.